2005
DOI: 10.1128/aac.49.1.220-229.2005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Tigecycline after Single and Multiple Doses in Healthy Subjects

Abstract: Tigecycline, a novel glycylcycline antibiotic, exhibits strong activity against gram-positive, gram-negative, aerobic, anaerobic, and atypical bacterial species, including many resistant pathogens, i.e., vancomycinresistant enterococci, methicillin-resistant Staphylococcus aureus and penicillin-resistant Streptococcus pneumoniae. The safety and tolerability of tigecycline administered as single or multiple doses or at various infusion rates were explored in three phase 1, randomized, double-blind, placebo-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

26
249
4
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 303 publications
(288 citation statements)
references
References 19 publications
26
249
4
4
Order By: Relevance
“…Our C max values are from 1.5 to 4 times higher than previously reported values at the same doses, and all AUC calculated values were approximately twofold higher than the reported values 17. Repeat analysis of plasma aliquots from several patients resulted in approximately the same concentrations.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…Our C max values are from 1.5 to 4 times higher than previously reported values at the same doses, and all AUC calculated values were approximately twofold higher than the reported values 17. Repeat analysis of plasma aliquots from several patients resulted in approximately the same concentrations.…”
Section: Discussioncontrasting
confidence: 48%
“…Increases in transaminases and pancreatic enzymes, and congestive heart failure have been reported in patients treated with tigecycline and are listed as rare drug reactions in the tigecycline package insert 22, 23. In addition, nausea and vomiting are the most frequently reported adverse events for the use of tigecycline 17. In this study, grade‐2 nausea, diarrhea and vomiting were reported in a total of five patients and judged to be possibly related to the treatment.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…To provide a pharmacologic correlate to these findings, we tested the effect of tigecycline (also known as Tygacil), an FDA-approved glycylcycline antibiotic known to inhibit the prokaryotic ribosome [31][32][33] and to interfere with mitochondrial translation in eukaryotes without affecting the translation of mitochondrial proteins encoded by nuclear genes (Supplementary Figure 2a). 34 The effect of tigecycline on viability of DLBCL subsets was examined at a dose range of 1-5 μM over a 24-72 h time course (Figures 3a-c; Supplementary Figure 2b).…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacological functional assays have shown that tigecycline inhibits bacterial protein synthesis with a potency that is 3-and 20-fold greater than that of minocycline and tetracycline, respectively 5 . This drug is currently registered only for intravenous use, and a twice-daily dosing regimen is relatively easy to administer and is generally well tolerated 7 . Clinical studies have shown that tigecycline possesses an expanded spectrum of in vitro and in vivo activity against Gram-positive, Gram-negative, atypical, anaerobic, and other difficult-to-treat pathogens 8 .…”
mentioning
confidence: 99%